(untitled) (Fiep Bulletin - online, 2013)
Quality study using an interview with a focus groups as tool. The aim was to describe and analyze perceptions of a family health team regarding the insertion of a six-month tai chi chuan program for elderly in family health units.T ai chi chuan is a traditional Chinese exercise practiced for centuries and part of Chinese traditional medicine consisting of a set of movements carried out in a slow and continuous way where mind and body are in constant interaction; has moderate intension and is often conducted as a collective exercising training. After conducting interviews we used content analysis as a method to treat data. In perceptions from family health team we noticed that the focus of basic care is still centered on the disease partially due to the great demand for services to communities. This study allowed the conclusion that tai chi chan may be a viable and pleasant alternative to maintain a healthy life style when providing care for people at aging processes and also that the practice may be important to the range of activities developed in strategies for family health and to Physical Education professionals in a multi-professional health team.